Bisphenol A (BPA) Content in Food and Beverage Plastic Packaging Perspective of Food Law and Consumer Protection - Wasiatul Qolbi (Veteran Law Review, 2023)
The packaging sector is an important industry. Packaging is used as a material to protect goods from external contamination. There are various kinds of packaging, one of which is often used is plastic packaging. In plastic packaging there is one of the BPA materials used in the plastic manufacturing process. This BPA content has the potential to be released and mixed with packaged food and drinks. While BPA is a content that can cause various diseases such as cancer. This study aims to determine the content of BPA in plastic packaging seen from the Law on Food and the Law on Consumer Protection. This study uses normative legal research that is descriptive analytical with a qualitative approach to primary data, secondary data and tertiary data which includes the content and structure of positive law. It is used as a reference in reviewing legal issues that are the object of study. The results of the study show that the BPA content in plastic packaging does not meet the packaging quality standards in accordance with the Law on Food. The Law on Food states that food packaging must use materials that do not endanger health. The Law on Consumer Protection also states that one of the rights of consumers is to have security and safety in consuming goods and services. The content of BPA which can cause various diseases is clearly not in accordance with the clauses in the Consumer Protection Act.